Mini incision appendectomy: an analysis of 70 cases - B. S., Sundaravadanan; P. B., Sudarshan; S., Prabu Shankar (International Surgery Journal, 2017)
Background: Appendicitis is a common surgical emergency world over, requiring surgical intervention immediately or as elective procedure to avoid complications. Various methods of appendisectomy are in practice, which includes conventional and laparoscopic appendectomy. One other method of appendectomy called mini appendisectomy is performed in selected patients. This study analyses the advantage, feasibility and utility of using mini incision Appendectomy for patients with appendicitis at Saveetha Medical College and Hospital, a teaching tertiary care hospital, Chennai, India. Methods: A total number of 70 cases diagnosed with appendicitis underwent this technique of mini incision appendisectomy mostly under spinal anesthesia. The study period was from 2013 to 2016, for 4 years duration. Patients detailed history, physical examination, operative details, post-operative complications, length of hospital stay, pain scores, analgesic requirements and patient satisfaction scores were collected. Results: Mini-incision appendectomy was performed in 70 patients with 2 cases (2.8%) which required an extension of the incision to 3.5 cm. Wound infection occurred in 2 patients which was treated conservatively. The average operating time was 25 minutes (20-45 minutes). No post-operative mortality. Patients had minimal post-operative pain. Conclusions: Hence mini incision appendectomy is a safe and advantageous technique in performing appendectomy in all hospitals.